Information systems architecture and technology : proceedings of 36th International Conference on Information Systems Architecture and Technology – ISAT 2015.: proceedings of 36th International Conference on Information Systems Architecture and Technology – ISAT 2015. Part III (2016) - Unknown
No abstract available